Empowerment Strategy Model For Coastal Horticultural Farmers through Technology Adoption and Innovation among Coastal in Ambal District, Kebumen Regency - Intan Wiji Ekawati; Ardiansyah Ardiansyah; Masrukin Masrukin; Nurul Hidayat; Lilik Kartika Sari (Journal of Business, Social and Technology, 2026)
Background: Coastal horticulture supports the food security and welfare of farmers in Ambal District, Kebumen, with great potential for cultivating melons, watermelons, and chili peppers. However, since the introduction of technology and innovation is still far from optimal, an effective farmer empowerment strategy is needed. Objective: This study aims to analyze the factors influencing technology adoption and innovation, assess the level of technology adoption and innovation among coastal horticultural farmers, and develop a strategic framework for farmer empowerment. Methods:  Using the Slovin method in six villages, a quantitative explanatory survey was conducted targeting 344 coastal horticultural farmers. The data was analyzed using structural equation modeling (SEM) with AMOS, investigating agricultural extension workers, social media, social norms, and digital literacy, utilizing social norms and digital literacy as mediators. Results:  Extension workers, social norms, and digital literacy have a significant and positive impact on technology adoption and innovation. Social media has no direct impact but delivers significant indirect effects through digital literacy. Social norms mediate the influence of extension workers. Adoption rates and innovation were highly rated (average = 3,808 points). Conclusion:  Social norms, digital literacy, and the spread of workers are the strongest correlations between technology adoption and innovation, but causal interpretation should be done carefully when considering cross-cutting design. Priority strategies include strengthening farm systems by farm corporations, improving digital literacy, and involving young farmers as drivers of modernization. This is supported by activated outreach services, technology-based regional development, and strong marketing and agricultural business partnerships.